Adsorption of Tributyl Phosphate on Silica Gel - V.F. Sazonova; M.A. Kojemyak; O.V. Perlova (Adsorption Science & Technology)
The adsorption behaviour of tributyl phosphate (TBP) on silica gel was studied. It was found that the adsorption isotherm shapes were complicated, being considered as S- and L-type isotherms according to the Giles classification. Adsorption itself was polymolecular and of a physical nature, the first adsorptive layer involving hydrogen bonding between the protons of surface silanol groups and the electron-donating oxygen atom of the adsorbate molecule. Subsequent adsorption layers were formed via van der Waals interaction. The free energy of adsorption of the system lay between −22.1 kJ/mol and −23.8 kJ/mol. The enthalpy change was negative and very small, i.e. −6.3 kJ/mol, while the entropy change was positive and in the range 53.9 J/(mol K) to 55.4 J/(mol K). The increase in entropy was explained in terms of the mobility of the TBP molecules in the adsorptive layer arising from their replacement on the silica gel surface by water molecules derived from the aqueous medium.